Presencia de pesticidas en la dieta como factor de riesgo para el parkinson esporádico - Sequeira Quesada, Carlos Mario (2014)
Parkinson is one of the most common neurodegenerative diseases worldwide. Nevertheless specific causes are up today not elucidated completely; as a matter of fact, this disease is understood nowadays as a result of the interaction between environmental influences such as exposure to pesticides, heritage and aging. In this research it is intended to review the bases and known principles of Parkinson’s disease, to explain some of the mechanisms for neuronal degeneration and identify specific pesticides that have proven causality between their use and Parkinson’s. It will also address the presence of those toxins in food of habitual intake and the risk it may hold, all of this as a result of a bibliographic research. The risk of having Parkinson’s disease was found to be greater when occupational-related or dietary exposure of organophosphate and organochlorine pesticides.  It is concluded that an incorrect use of pesticides can produce water, soil and food contamination increasing the risk of suffering Parkinson’s disease.